Creative food cycles - Book 1. - (:unkn) unknown (My University, 2020)
Creative Food Cycles zielt auf eine aktive Rolle von Architektur, Städtebau und Design für nachhaltige urbane Nahrungskreisläufe.Das Projekt verbindet Forschung mit experimentellem Prototyping, kulturellen Aktionen und gesellschaftlichem Dialog. Gefördert durch das Programm Kreatives Europa durch die Europäische Union von 2018 bis 2020 koordiniert das Institut für Entwerfen und Städtebau, Prof. Jörg Schröder eine Kooperation mit den Projektpartnern aus Barcelona und Genua.

Creative Food Cycles addresses three interconnected fields of innovation: 1. Creative Food Cycles AS DRIVER FOR URBAN RESILIENCE. Fostering novel and adaptive Food Cycles as driver for resilience in cities, economy, society, and culture. 2. Creative Food Cycles AS SOCIAL INNOVATION. Extending civic participation in Food Cycles toward active engagement, new urban communities, and new models of social entrepreneurship. 3. Creative Food Cycles BASED ON DIGITAL TECHNOLOGIES. Experimenting with interactive devices and digital protocols with a strong cultural and social impact, as an empowering force of Food Cycles. Creative Food Cycles is funded by the European Union in the Creative Europe programme from 2018 to 2020. The project is coordinated by the Institute for Design and Urban Planning of the Leibniz University of Hannover and pre- formed with the project partners Institute for Advanced Architecture of Cat- alonia IAAC Barcelona/Spain and Department of Architecture and Design of the University of Genoa/Italy. Creative Food Cycles combines research with experimental prototyping, cultural actions and social dialogue.
Keywords: Nachhaltige Stadtentwicklung; Lebensmittelversorgung; Nahrungsmittelproduktion; Kreislaufwirtschaft; Resilienz; Stadt-Land-Beziehung; Digitalisierung; Abfallvermeidung